The biomechanical structure of swim start performance - Fischer, S.; Kibele, A. (Sports Biomechanics, 2016)
The aim of this study was to analyse the significance of various biomechanical parameters in swim start performance for the grab and track start techniques. To do so, structural equation models were analysed, incorporating measurements for the take-off phase, flight phase and entry phase. Forty-six elite German swimmers (18 female and 28 male; age: 20.1 ± 4.2 yrs; PB (100 m Freestyle): 53.6 ± 2.9 s) participated in the study. Their swim start performance was examined within a 25-m sprint test. Structural equation modelling was conducted in separate models for the block time, flight time and water time and in a combined model for swim start time. Our main finding was that swim start time is predominantly related to water time and determined to a lesser extent by block time and flight time. We conclude that more emphasis should be given to the water immersion behaviour and the gliding phase when analysing swim start performance. Furthermore, significant differences were found between the grab start and track techniques as regards the biomechanical parameters representing the take-off phase and water phase.